2022
DOI: 10.1007/s44200-022-00013-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Layer-Specific Residual Stresses in Arterial Mechanics: Analysis via a Novel Modelling Framework

Abstract: The existence of residual stresses in unloaded arteries has long been known. However, their effect is often neglected in experimental studies. Using a recently developed modelling framework, we aimed to investigate the role of residual stresses in the mechanical behaviour of the tri-layered wall of the pig thoracic aorta. The mechanical behaviour of the intact wall and isolated layers of n = 3 pig thoracic aortas was investigated via uniaxial tensile testing. After modelling the layer-specific mechanical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Given that the relative contribution of the arterial layers to the wall mechanical response is pressuredependent(Giudici et al 2021a; Giudici and Spronck 2022), a more complex multi-layered cbQLV model with layer-speci c parameters could further improve the description of the non-linear viscoelasticity of arteries. Furthermore, because of the single-layer thin-wall assumption, tractation of residual stresses is greatly simpli ed in our modelling framework; because of the inclusion of deposition stretches in the model, each constituent may not be stress-free in κ u , but the transmural distribution of residual stresses cannot be captured(Giudici and Spronck 2022;Zhang et al 2022).…”
mentioning
confidence: 99%
“…Given that the relative contribution of the arterial layers to the wall mechanical response is pressuredependent(Giudici et al 2021a; Giudici and Spronck 2022), a more complex multi-layered cbQLV model with layer-speci c parameters could further improve the description of the non-linear viscoelasticity of arteries. Furthermore, because of the single-layer thin-wall assumption, tractation of residual stresses is greatly simpli ed in our modelling framework; because of the inclusion of deposition stretches in the model, each constituent may not be stress-free in κ u , but the transmural distribution of residual stresses cannot be captured(Giudici and Spronck 2022;Zhang et al 2022).…”
mentioning
confidence: 99%
“…In this study, tri-layered constitutive modelling was used to investigate how observed regional differences in layer-specific mechanical behaviour affect the macroscopic response of the aortic wall. The existence of layer-specific residual stresses is known (Greenwald et al, 1997;Holzapfel et al, 2007;Peña et al, 2015), and their estimation represents the crucial link between the isolated layers' mechanical behaviour and that of the tri-layered wall (Giudici and Spronck, 2022). The most common approach to modelling of residual deformation consists of directly quantifying shape changes that strips of individual layers undergo when isolated from the wall (Díaz et al, 2021;Holzapfel et al, 2007).…”
Section: Figmentioning
confidence: 99%
“…The isolation and tensile testing of individual arterial layers is a useful technique that allows investigating how inter-regional differences in layers' microstructure affects their mechanical properties. This experimental technique has been used at different locations of the arterial tree and in different species, including the human thoracic and abdominal aorta (Teng et al, 2015;Weisbecker et al, 2012), carotid artery (Sommer et al, 2010), coronaries (Holzapfel et al, 2005) and ascending aortic aneurysm (Deveja et al, 2018;Sassani et al, 2015), and the pig descending thoracic aorta (Giudici et al, 2021a;Giudici and Spronck, 2022;Peña et al, 2015). Further, fitting the experimental data using constitutive models whose parameters aim to describe the mechanical behaviour of the wall constituents (typically elastin and collagen) provides additional quantitative information on region-and layer-specific arterial structure-mechanics (Peña et al, 2015;Weisbecker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been well documented in the literature that residual stresses are present in arterial vessels 33–38 . These residual stresses have a significant impact on the distribution of physiological stresses throughout the vessel wall and tend to homogenize the stress distribution within each arterial layer in the physiological state.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Furthermore, it has been well documented in the literature that residual stresses are present in arterial vessels. [33][34][35][36][37][38] These residual stresses have a significant impact on the distribution of physiological stresses throughout the vessel wall and tend to homogenize the stress distribution within each arterial layer in the physiological state. Numerous studies have demonstrated that the inclusion of residual stresses under physiological loading conditions substantially reduces the variation in both the circumferential and axial residual stress within the vessel wall.…”
Section: Introductionmentioning
confidence: 99%